Comparison Analysis of Nepali News Classifier - Koshish Shrestha; Kabita Khanal; Isha Shrestha; Neerav Shrestha; Kunjan Amatya (KEC Journal of Science and Engineering, 2025)
With the growing volume of daily generated Nepali news content, which predominantly exists in unstructured formats, the need arises to effectively categorize and label this information. Considering this challenge, our system employs various Machine Learning algorithms such as Logistic Regression, Random Forest Algorithm, Neural Networks, etc., to automatically classify Nepali news into predefined categories and evaluate the efficiency of the model, which offers us a comparative analysis of these various algorithms.